1985
DOI: 10.1086/268931
|View full text |Cite
|
Sign up to set email alerts
|

The Power of The Right Stuff: A Quasi-Experimental Field Test of the Docudrama Hypothesis

Abstract: HOLLYWOOD produced a major film lionizing the heroics of a presidential candidate at the start of the 1984 campaign. The implications were unprecedented, and as a result, this motion picture-The Right Stuffgenerated great interest among political analysts. The key question was, as the cover of Newsweek put it, "Can a Movie Help Make a President?"For students of political communications, The Right Stuff raised a more enduring issue that went beyond the immediate campaign consequences of the movie. That issue ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 1 publication
0
18
1
Order By: Relevance
“…8 However, the findings of this study of The Day After suggest that too little attention has been paid to oblique or corollary effects. Just because viewers do not accept the exact message or learn the particular lesson predicted by the researcher does not mean that no lessons have been learned.…”
Section: Communication Theory and Unexpected Effectscontrasting
confidence: 55%
“…8 However, the findings of this study of The Day After suggest that too little attention has been paid to oblique or corollary effects. Just because viewers do not accept the exact message or learn the particular lesson predicted by the researcher does not mean that no lessons have been learned.…”
Section: Communication Theory and Unexpected Effectscontrasting
confidence: 55%
“…The second limitation is that the documented effects were for only a short period of time following viewing of the film; it is possible that these effects may not persist over time. In their study of The Right Stuff, Adams et al (1985) did not find any long-term effects; however, this may have been due to other events occurring in the interim. Third, this study looks at exposure in a single instance.…”
Section: Discussionmentioning
confidence: 83%
“…There are several empirical examples of this type of phenomenon. For example, in their study of the film The Right Stuff, Adams et al (1985) found that individuals developed more favorable attitudes toward John Glenn, a candidate for the Democratic presidential nomination, after exposure to the pro-Glenn film. Kaid (1997) found in her experimental study of the effects of exposure to presidential television advertising that Democrats became more positive toward Clinton after viewing a Clinton advertisement, while Republicans became more positive toward Dole after viewing a Dole advertisement.…”
Section: Selective Exposure and Media Effectsmentioning
confidence: 99%
“…Although there are theoretical reasons to predict a link between the selection of likeminded media outlets and polarized attitudes, the empirical evidence to date is inconclusive. First, although a number of studies have found evidence of a link between media exposure and polarization (Adams et al, 1985; Bimber & Davis, 2003; Druckman & Parkin, 2005; Jones, 2002; Lavine, Borgida, & Sullivan, 2000; Mendelsohn & Nadeau, 1996; Stroud, 2007; Taber & Lodge, 2006), there are exceptions where scholars have found no evidence of polarization (see, e.g., Ball‐Rokeach, Grube, & Rokeach, 1981; Paletz, Koon, Whitehead, & Hagens, 1972) or where scholars have raised questions about whether likeminded media exposure enhances polarization (Meffert, Chung, Joiner, Waks, & Garst, 2006). Second, none of the studies to date have attempted to consider people's media exposure patterns comprehensively.…”
Section: Partisan Selective Exposure Leads To Polarizationmentioning
confidence: 99%